Perancangan dan Analisis Tekno Ekonomi PLTS On-Grid System sebagai Supply Energi Listrik Masjid Al-Istiqamah Politeknik Negeri Jember - Argo Tri Winnarni; Risse Entikaria Rachmanita (Politeknik Negeri Malang, 2024)
The increasing energy demand is directly proportional to the growing population and technological advancements. The energy needs in Indonesia largely rely on fossil fuels, which are limited and environmentally unfriendly due to their emission characteristics. The potential of solar energy in Indonesia is around 4.8 kWh/m2, making it a renewable and environmentally friendly energy source that can be utilized for Solar Power Plants (PLTS). The aim of this research is to design an on-grid PLTS system and conduct techno-economic analysis using PVSyst software. This design requires 14 Longi Solar/LR5-72HPH-550M solar panels and 1 Huawei SUN2000-6KTL-M1 inverter. The estimated electricity production is 10,852 kWh/year in the first year. The initial investment cost for this PLTS system is Rp. 120,343,517.00, with estimated savings over 25 years amounting to Rp. 270,115,412.00. Economically, based on the feasibility analysis using the LWBP tariff calculation method, the NPV is Rp. 2,174,707.00, BCR is 1.68, and PBP is 11.8 years. Meanwhile, based on the feasibility analysis using the LCoE calculation method, the NPV is Rp. 74,877,690.00, BCR is 2.61, and PBP is 7.5 years. Based on the conducted research, the construction of this PLTS is deemed feasible to be implemented.